Gender-Related Differences in Regional Cerebral Glucose Metabolism in Normal Aging Brain - Feng, Bei; Cao, Jiang; Yu, YaPing; Yang, HaiYan; Jiang, YangHongYan; Liu, Ying; Wang, Rong; Zhao, Qian (Frontiers in Aging Neuroscience, 2022)
Objectives: This study was aimed to investigate the gender-related differences of regional cerebral glucose metabolism in healthy people along the age using 18F-FDG PET/CT. Methods: We recruited 344 healthy volunteers, including 217 males and 127 females (age range: 40-89 years old). All subjects underwent fluorine-18 fluorodeoxyglucose(18F-FDG) positron emission tomography (PET). All the data were divided into four groups for each ten years old. Each participant was carefully screened from PET, MR and other examinations in order to exclude the abnormalities, such as neurodegenerative or psychiatric disorders, alcohol/abuse, cerebral vascular disorders, metabolic disease like diabetes mellitus and hyperthyroidism, and other systemic malignancies. The 40 to 50 years old group was set as the baseline group. Statistical parametric mapping (SPM) analysis was employed to illustrate the differences among groups. Results: Compared to the baseline group, whatever in cohort or different gender groups, the decrease of brain glucose metabolism was shown in bilateral frontal lobe, anterior cingulate gyrus, bilateral temporal lobe. In males, the regions of decreased metabolism were bilateral frontal lobe, caudate nucleus, cingulate gyrus, whereas that of females were left occipital lobe, cerebellum and thalamus. However, the overall decrease of brain metabolism in men and women were all began from the age of 60s, an aggravated decrease from 70s was only observed in males. Conclusion: 1. An obviously decreased brain metabolism was found from 60 years old, especially in the bilateral frontal lobe, bilateral temporal lobe, inferior cingulate gyrus. 2. We found specific brain metabolic differences between genders, including the caudate nucleus region in male and the occipital lobe region in female. 3. The aging trend is different between genders.